Partisipasi Dan Sikap Masyarakat Desa Manukaya Terhadap Pengelolaan Daya Tarik Wisata Tirta Empul Tampaksiring Kabupaten Gianyar - I Made Edi Suandana; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
Tirta Empul Temple is one of the templesin balithat become a tourist attraction and crowded by tourists either domestic tourists or foreign tourists. The tourist attraction of Tirta Empul is unique because besides being a place of worship for Hindus as well as a holy bath. Besides that, Tirta Empul Temple also has its own unique history and architecture. Tirta Empul Tourist Attraction is managed by the Manukaya VillageCommunityand from the Gianyar Regency Government. This study aims to find out how the participation of Manukaya Village community in managing Tirta Empul Tourism Attraction. Then to find out the response of the Manukaya Village community to the Management of Tirta Empul Tourism Attraction. In this study data was collected by conducting direct observations to the field and conducting interviews with the community. The sample was determined using purposive sampling technique to determine the sample. And the data were analyzed using qualitative descriptive data analysis techniques The results of this study indicate that the participation of the community of Manukaya Village towards the management of the attraction of Tirta Empul can be seen from the involvement of the local community directly managing the Tourist Attraction, through their obligation to work there alternately. All heads of families and youths in the Manukaya Traditional Village will have their turn to serve in the attraction of Tirta Empul, starting from those who are nurturing and those who do not have obligations in the traditional village or called Balu Angkep. The Aduk Manukaya Village Community Let all participate in the management of Tirta Empul's tourist attraction, both from planning, organizing, mobilizing people, and supervising. Overall the response as attitude of the Manukaya Village community to the management of Tirta Empul Tourism Attraction is look positive without complain. Although there are two groups included in this area, but participated groups directly in the management is Desa Adat Manukaya. Group desa adat Malat accepted with comfortable this situation. Keywords:participation, response, management.